Alkali-corrosion synthesis and excellent DSSC performance of novel jujube-like hierarchical TiO2 microspheres. (5th March 2018) - Xiao, Jiajia; Li, Po; Wen, Xiaogang
Abstract: Novel jujube-like hierarchical TiO2 microspheres (HTMs) were synthesized by an alkali-corrosion process of titanium phosphate (Ti2 O3 (H2 PO4 )2  · 2H2 O) microspheres. The hierarchical titanium phosphate microsphere (HTPM) intermediates consisting of nanoflakes with a thickness of 20 nm were firstly prepared by a facile hydrothermal method. After reacting with diluted NaOH at low temperature and atmospheric pressure, followed by subsequent acid washing and a calcination process, the HTPM intermediates were transformed to TiO2 with the microsphere morphology well retained, while the nanoflakes became porous, and some new nanowires were formed between the nanoflakes. Finally, HTMs consisting of porous nanoflakes and nanowires were obtained. The possible growth mechanisms of HTPMs and HTMs are discussed. The HTMs demonstrate high specific surface area and excellent light-scattering ability. The performance of the dye sensitized solar cells (DSSCs) of the HTMs synthesized under different conditions is studied, and a total conversion efficiency of up to 8.93% was obtained. The improved DSSC performance was attributed to the enhanced dye loading, light-scattering, and charge transporting ability of the HTMs with a unique hierarchical nanostructure.